The effect of gut microbiota-derived carnosine on mucosal integrity and immunity in broiler chickens challenged with Eimeria maxima - Inkyung Park; Hyoyoun Nam; Youngsub Lee; Samiru S. Wickramasuriya; Alexandra H. Smith; Thomas G. Rehberger; Hyun S. Lillehoj (Poultry Science, 2024)
ABSTRACT: In the first study, an in vitro culture system was developed to investigate the effects of carnosine on macrophage proinflammatory cytokine response using an established chicken macrophage cell line (CMC), gut integrity using a chicken intestinal epithelial cell line (IEC), muscle differentiation in quail muscle cells (QMCs) and primary chicken embryonic muscle cells (PMCs), and direct anti-parasitic effect against Eimeria maxima sporozoites. Cells to be tested were seeded in 24-well plates and treated with carnosine at 4 different concentrations (0.1, 1.0, and 10.0 µg). After 18 h of incubation, cells were harvested to measure gene expression of proinflammatory cytokines in CMC, tight junction (TJ) proteins in IECs, and muscle cell growth markers in QMCs and PMCs. In vivo trials were conducted to investigate the effect of dietary carnosine on disease parameters in broiler chickens challenged with E. maxima. One hundred and twenty male broiler chickens (0-day-old) were allocated into 4 treatment groups: 1) basal diet without infection (NC), 2) basal diet with E. maxima infection (PC), 3) carnosine at 10.0 mg/kg feed with PC (HCS), and 4) carnosine at 1.0 mg/kg feed with PC (LCS). All groups except NC were orally infected with E. maxima on d 14. Jejunal samples were collected for lesion scoring and jejunum gut tissues were used for transcriptomic analysis of cytokines and TJ proteins. In vitro, carnosine treatment significantly decreased IL-1β gene expression in CMC following LPS stimulation. In vivo feeding studies showed that dietary carnosine increased BW and ADG of chickens in E. maxima-infected groups and reduced the jejunal lesion score and fecal oocyst shedding in HCS group. Jejunal IL-1β, IL-8, and IFN-γ expression were suppressed in the HCS group compared to PC. The expression levels of claudin-1 and occludin in IECs were also increased in HCS following carnosine treatment. In conclusion, these findings highlight the beneficial effects of dietary carnosine supplementation on intestinal immune responses and gut barrier function in broiler chickens exposed to E. maxima infection.